Temporal variability determines phytoplankton structure over spatial organization in a large shallow heterogeneous subtropical lake. Issue 3 (1st January 2016) - Freitas-Teixeira, Lacina M.; Bohnenberger, Juliana E.; Rodrigues, Lucia R.; Schulz, Uwe H.; da Motta-Marques, David; Crossetti, Luciane O.
Abstract: Spatial heterogeneity is associated with the temporal variability of the habitat and may affect the structural patterns of biological communities. This study evaluated the influence of spatial and temporal heterogeneity on the phytoplankton structure in a large shallow subtropical lake, Lake Mangueira in southern Brazil (Zmax = 6 m; length = 90 km; width = 3–10 km). The lake is continuous warm polymictic, oligo-mesotrophic, under the direct influence of an adjacent wetland on the north, and has extensive aquatic macrophyte beds. Samples for abiotic and biological analyses were taken quarterly for 2 years at 19 points at the water subsurface, comprising the pelagic and littoral zones and the southern, central, and northern areas of the lake. The phytoplankton structure was analyzed with measurements of chlorophyll, biomass, richness, diversity, and descriptor species. Of the 117 phytoplankton species identified, Cyanobacteria (e.g., , , Chroococcus limneticus, Aphanocapsa conferta, Aphanothece smithii, and Planktolyngbya contorta ) was the major group in all areas and both zones of the lake. Total biomass levels were highest in the northern area, whereas the richness and the descriptor species showed no clear spatial differences. A redundancy analysis (RDA) indicated strong temporal organization of the species according to the abiotic conditions, indicating that the high level of temporal variability due to local hydrodynamics was the main factor structuring the phytoplankton community in Lake Mangueira during the study period.